Diversity of Macroalgae Species on Pramuka Island and Kotok Besar Island, Thousand Island Regency, DKI Jakarta Province - Ainisyifa, Ulfa; Setia, Tatang Mitra; Kusumahadi, Khoe Susanto; Handayani, Sri (Universitas Nasional Jakarta, 2025)
Indonesia's coastal and marine ecosystems, including coral reefs, mangroves, and seagrass beds, play critical roles in maintaining biodiversity and ecological balance while providing essential ecosystem services such as coastal protection and food resources. This study evaluates the health of aquatic ecosystems on Pramuka Island and Kotok Besar Island by assessing macroalgal diversity and water quality parameters. Using a survey method with quadratic transects, we analyzed species composition, Shannon-Wiener diversity index, and important value index (IVI) of macroalgae, alongside measurements of physical (temperature, salinity, brightness, depth, current speed) and chemical (pH, dissolved oxygen) water parameters. Results identified 26 macroalgal species on Pramuka Island and 19 on Kotok Besar Island, with moderate diversity indices (H’=2.64 and H’=2.26, respectively). The dominant species were Halimeda macroloba (Chlorophyta) and Hypnea asperi (Rhodophyta) on Pramuka Island, and Halimeda macroloba (Chlorophyta) and Sargassum binderi (Phaeophyta) on Kotok Besar Island. Water quality across both islands remained within optimal ranges for macroalgal growth. These findings underscore the ecological significance of macroalgal communities as bioindicators and highlight the need for targeted conservation strategies to preserve these ecosystems amid rising anthropogenic pressures.